2020
DOI: 10.21043/iqtishadia.v13i2.7748
|View full text |Cite
|
Sign up to set email alerts
|

The Stability of the Indonesian Sharia Stock Index to Economic Shocks

Abstract: <p>The stock market has a strategic role in the development of a country's economy in the era of globalization, including the Islamic stock market. The rapid growth of the Islamic stock market, especially in developing countries, is a historical record in Indonesia's financial sector. This study aims to analyze the factors that influence the return of the Indonesian Sharia Stock Index (ISSI) in the short and long term, how long shocks occur, and how much the contribution of these factors. This study uses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 29 publications
1
6
0
4
Order By: Relevance
“…Furthermore, it is important to note that the results of this research support previous studies indicating the positive impact of crude oil prices on the Sharia stock market in Indonesia Indonesia (Bawono & Mutaqin, 2019;Masrizal et al, 2019;Zahrok et al, 2021). However, the literature also reflects divergent opinions, with some studies concluding a negative or insignificant impact of crude oil prices on Sharia stocks (Antonio et al, 2021;Fitrianto, 2020;Mahfudz & Nurhadi, 2021;Mubarok et al, 2020;Nawindra & Wijayanto, 2020;Noval, 2022;Rokhaniyah, 2020). This indicates the complexity of the relationship between crude oil prices and the Sharia stock market, which can be influenced by a number of economic variables and policies.…”
Section: Effect Of Crude Oil Prices On Sharia Stock Marketsupporting
confidence: 80%
See 2 more Smart Citations
“…Furthermore, it is important to note that the results of this research support previous studies indicating the positive impact of crude oil prices on the Sharia stock market in Indonesia Indonesia (Bawono & Mutaqin, 2019;Masrizal et al, 2019;Zahrok et al, 2021). However, the literature also reflects divergent opinions, with some studies concluding a negative or insignificant impact of crude oil prices on Sharia stocks (Antonio et al, 2021;Fitrianto, 2020;Mahfudz & Nurhadi, 2021;Mubarok et al, 2020;Nawindra & Wijayanto, 2020;Noval, 2022;Rokhaniyah, 2020). This indicates the complexity of the relationship between crude oil prices and the Sharia stock market, which can be influenced by a number of economic variables and policies.…”
Section: Effect Of Crude Oil Prices On Sharia Stock Marketsupporting
confidence: 80%
“…In contrast, Bawono & Mutaqin (2019), Masrizal, Ubaidillah Al Mustofa, &Zahrok et al (2021) concluded that crude oil prices have a positive effect on the Sharia Stock Market in Indonesia. However, other studies conducted by Mahfudz & Nurhadi (2021), Mubarok, Al Arif, & Mufraini (2020), Nawindra &Wijayanto (2020), andNoval (2022) indicate that crude oil prices do not have a significant impact on the Sharia Stock Market in Indonesia.…”
Section: Crude Oil Prices and Sharia Stock Marketmentioning
confidence: 83%
See 1 more Smart Citation
“…Penelitian terdahulu yang dilakukan oleh Deng, Xu, & Lee (2022) menemukan bahwa kebijakan pembatasan sosial dalam rangka mengurangi penyebaran COVID-19 membuat kinerja pasar modal menjadi lambat, bahkan ke arah negatif. Selain itu, dalam penelitian Indrayono (2021) (Mubarok, Al Arif, & Mufraini, 2020). Dari fakta tersebut, maka diformulasikan hipotesis sebagai berikut : H2 : Tidak terdapat perbedaan pada ISSI sebelum dan ketika era COVID-19.…”
Section: Abstrakunclassified
“…The Indonesian Stock Exchange (BEI) lists every Sharia Stock Index. For example, several studies related to Indonesia shariah stock index can be found in Agustin (2019), Mubarok et al, (2020), and also Alam et al, (2020).…”
Section: Introductionmentioning
confidence: 99%